Implementasi Program Bola Voli Untuk Meningkatkan Aktivitas Fisik Dan Kesehatan Dikalangan Remaja - Mile, Sarjan; Datau, Suriyadi; Kadir, Sulasikin Sahdi; Tumaloto, Ella H; Ruslan, Ruslan (Universitas Negeri Gorontalo, 2025)
The decline in physical activity among adolescents has become an increasingly concerning issue, largely due to technological advancements and sedentary lifestyles. This community service program was implemented in Hutuo Village, Limboto District, Gorontalo Regency, with the aim of enhancing physical activity and fitness among adolescents through volleyball training. The program involved 30 adolescents aged 13–17 years and was conducted over a two-week period with training sessions held twice a week. The implementation methods included delivering fundamental volleyball concepts, hands-on practice sessions, and evaluations using pre-tests and post-tests. Evaluation results indicated a significant improvement in the participants' physical activity levels, with average scores increasing from 58.3 in the pre-test to 74.6 in the post-test. Additionally, there was a noticeable rise in participants’ enthusiasm and motivation to engage in physical activity independently. This program is expected to positively contribute to promoting an active and healthy lifestyle among adolescents in the area.